Salivary diagnosis of Zika Virus using ATR-FTIR-spectroscopy - Oliveira, Stephanie Wutke (2021)
Zika Virus (ZIKV) diagnosis is currently performed by an invasive, painful, and costly procedure using molecular biology. Consequently, the search for a non-invasive, more cost-effective (reagent free), and sustainable method for ZIKV diagnosis is of great relevance. It is critical to prepare the global strategy for the next ZIKV outbreak and its devastating consequences, particularly in pregnant women. Fourier-transform infrared (ATR-FTIR) spectroscopy was used to discriminate systemic diseases using saliva, however, the salivary diagnostic application in viral diseases is unknown. To test this hypothesis, we intradermally challenged interferon-gama gene knockout C57/BL6 mice with ZIKV (50 µl,105 FFU, n=7) or vehicle (50 µl, n=7). Saliva samples were collected at day 3 (due to the peak of viremia) and spleen were also harvested. The changes in salivary spectral profile were analyzed by T Test (p<0.05), multivariate analysis and the diagnostic capacity by ROC curve. The ZIKV infection was confirmed by Real time PCR at spleen sample. The infrared spectroscopy coupled to univariate analysis suggested the vibrational mode at 1547 cm-1 as potential candidate to discriminate ZIKV and control salivary samples. Three PCs explained 93.2% of cumulative variance in PCA analysis and the spectrochemical analysis with LDA achieved an accuracy of 93.3%, with a specificity of 87.5% and sensitivity of 100%. The PCA-SVM analysis showed 100% of discrimination between both classes. Our results suggest that ATR-FTIR applied to saliva might have high accuracy in ZIKV diagnosis with potential as a non-invasive and cost-effective diagnostic tool.